Identifikasi Kestabilan Tanggul Waduk Desa Kemuja Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner - Asisah, Tina; Widyaningrum, Yekti; Indriawati, Anisa (Jurusan Fisika, Universitas Bangka Belitung, 2024)
Kemuja Village Reservoir is one of the reservoirs located in Kemuja Village, West Mendo District, Bangka Regency, which was built in 2015. On the sides of the Kemuja Village Reservoir, there are embankments that are used to prevent flooding of rice fields. Based on the initial survey, the height of the embankment from the ground is ±2.6 m and the water level is ±1 m above the surface. This study aims to identify the stability of the Kemuja Village reservoir embankment based on 2D modeling using the Wenner configuration resistivity geoelectric method with a spacing of 8 m between electrodes. Based on 2D modeling, the Kemuja Village reservoir embankment has good stability on all tracks, except on track 1 at a depth of 0 m - 1 m with a measurement distance of 10 m - 14 m, track 2 at a depth of 0 m - 1 m with a measurement distance of 36 m - 40 m, track 3 at a depth of 0.5 m - 2 m with a measurement distance of 6 m - 8 m; 0 m - 1.5 m with a measurement distance of 12 m - 16 m and 0 m - 2 m with a measurement distance of 28 m - 30 m, traverse 4 at a depth of 0 m - 1 m with a measurement distance of 8 m - 10 m and 0 m - 2 m with a measurement distance of 44 m - 48 m.